Prolonged survival of pancreatic islet allografts mediated by adenovirus immunoregulatory transgenes. - Efrat, S (1995)
The adenovirus (Ad) early region 3 (E3) genes code for at least four proteins that inhibit the host immune responses mediated by cytotoxic T lymphocytes and tumor necrosis factor alpha. To evaluate the potential use of these immunoregulatory viral functions in facilitating allogeneic cell transplantation, the Ad E3 genes were expressed in pancreatic beta cells in transgenic mice under control of the rat insulin II promoter. Transgenic H-2b/d (C57BL/6 x BALB/c) islets, expressing the Ad E3 genes, remained viable for at least 94 days after transplantation under the kidney capsule of BALB/c (H-2d) recipients. Nontransgenic H-2b/d control islets were rejected as anticipated between 14 and 28 days. Histological analysis of the transplanted transgenic islets revealed normal architecture. Immunohistochemical studies with antisera to islet hormones revealed the presence of both beta and non-beta islet cells, suggesting a propagation of the immunosuppressive effect of Ad proteins from beta cells to other islet cells. The use of viral genes, which have evolved to regulate virus-host interactions, to immunosupress the anti-genicity of donor transplant tissue suggests additional ways for prolonging allograft survival. In addition, these findings have implications for designing Ad vectors for gene therapy.